2017
DOI: 10.1159/000473888
|View full text |Cite
|
Sign up to set email alerts
|

In IgA Nephropathy, Glomerulosclerosis Is Associated with Increased Urinary CD80 Excretion and Urokinase-Type Plasminogen Activator Receptor-Positive Podocyturia

Abstract: Background: Podocyturia may determine the evolution to podocytopenia, glomerulosclerosis, and renal failure. According to the Oxford classification of IgA nephropathy (IgAN), the S1 lesion describes glomerulosclerosis. Urokinase-type plasminogen activator receptor (uPAR) participates in podocyte attachment, while CD80 increases in glomerulosclerosis. We measured uPAR-positive urinary podocytes and urinary CD80 (uCD80) in controls and in IgAN subjects with M1E0S0T0 and M1E0S1T0 Oxford scores to assess a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…16 Podocyturia and podocyte-specific molecules shed into the urine may yet prove valuable tools for pathophysiologic investigations in IgAN, but such studies have suffered from lack of standardization, cellular instability, and lack of suitable podocyte markers. 17,18 Debate also continues over the importance of vascular lesions in IgAN, in particular those associated with endothelial injury and thrombotic microangiopathy. 19,20 The reported fraction of IgAN patients with morphologic lesions of thrombotic microangiopathy varies greatly from 2% to 50%.…”
Section: The Oxford Classification Of Iganmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Podocyturia and podocyte-specific molecules shed into the urine may yet prove valuable tools for pathophysiologic investigations in IgAN, but such studies have suffered from lack of standardization, cellular instability, and lack of suitable podocyte markers. 17,18 Debate also continues over the importance of vascular lesions in IgAN, in particular those associated with endothelial injury and thrombotic microangiopathy. 19,20 The reported fraction of IgAN patients with morphologic lesions of thrombotic microangiopathy varies greatly from 2% to 50%.…”
Section: The Oxford Classification Of Iganmentioning
confidence: 99%
“…23,24 A number of putative IgAN-specific biomarkers were discussed, including serum levels of Gd-IgA1, Gd-IgA1-specific autoantibodies, and IgA-IgG immune complexes; urinary Gd-IgA1, CD89, CD71, and podocyte urokinase-type plasminogen activator receptor. 18,[25][26][27] Each of these biomarkers now needs to be evaluated in the new risk prediction model that provides a study platform to see whether they add value in predicting risk and guiding clinical decision making in IgAN.…”
Section: Biomarkersmentioning
confidence: 99%
“…In nephrotic urines, plasmin is elevated due to the upregulated action of uPA, and its receptor uPAR is highly expressed in urinary podocytes[ 21 , 22 ]. These findings suggest that uPAR is involved in podocyte detachment, probably via activation of αVβ3-integrin[ 16 , 23 , 24 ]. Employing immunofluorescent microscopy, we have demonstrated that in patients with IgA nephropathy and Fabry disease, uPAR is present in the cytoplasm of urinary podocytes.…”
Section: Mechanisms Of Podocyte Detachmentmentioning
confidence: 99%
“…Employing immunofluorescent microscopy, we have demonstrated that in patients with IgA nephropathy and Fabry disease, uPAR is present in the cytoplasm of urinary podocytes. In the case of IgA nephropathy, the number of uPAR + detached podocyte is significantly higher than controls and in patients with glomerular sclerotic lesions compared to those without (M1E0S1T0 vs M1E0S0T0 according to Oxford classification)[ 24 ]. Moreover, by western blot analysis as well as by PCR techniques we have confirmed the presence of elevated concentrations of uPAR in Fabry podocytes[ 23 ].…”
Section: Mechanisms Of Podocyte Detachmentmentioning
confidence: 99%
“…Urokinase-type plasminogen activator receptor (uPAR) may participate in podocyte attachment. uPAR could play a fundamental role in the process of irreversible podocyte detachment through progression to kidney failure via glomerular podocytopenia and glomerulosclerosis [68]. In this sense, the use of amiloride could be useful to avoid podocyte detachment by blocking uPAR synthesis.…”
Section: Histopathological Characteristics Prognostic and Future Thementioning
confidence: 99%